Impact of the COVID‐19 Outbreak on the Incidence of Autoimmune Encephalitis and Paraneoplastic Neurological Syndromes Associated Antibodies in Singapore - Rui Ling Rena Lau; Karine Su Shan Tay; Seyed Ehsan Saffari; Patricia Yut Wan Wong; Mei Ting Lim; Angelia Swee Hoon Koe; Jeanne May May Tan; Kok Pin Yong; Kevin Tan; Josiah Yui Huei Chai; Tianrong Yeo (Brain and Behavior)
ABSTRACT Background Emerging evidence suggests a potential association between COVID‐19 and autoimmune encephalitis (AE). We aimed to evaluate the positivity rate of AE‐ and paraneoplastic neurological syndromes (PNS)‐associated antibodies in relation to COVID‐19. Methods We investigated the frequency and incidence of AE‐ and PNS‐associated antibodies amongst clinical tests performed at the National Neuroscience Institute, Singapore, before and during the COVID‐19 pandemic. Antibodies against surface‐exposed antigens associated with AE were tested using cell‐based assays; antibodies against intracellular antigens in PNS were detected by immunoblot and tissue‐based assays. Results A total of 87 of 4347 samples and 29 of 3393 samples tested for AE‐ and PNS‐associated antibodies, respectively, were positive. A spike in the incidence of AE‐associated antibodies was observed in 2020 at 4.92 (95% CI, 3.05–7.53) per 1,000,000 person‐years, coinciding with the first year of the COVID‐19 “pandemic outbreak.” The cumulative incidence in the “pre‐pandemic” period from 2017 to 2019 was 2.44 (95% CI, 1.66–3.46) per 1,000,000 person‐years (p = 0.034, vs. “pandemic outbreak”), and in the “mid to late pandemic” period from 2021 to 2023, this was 2.74 (95% CI, 1.91–3.82) per 1,000,000 person‐years (p = 0.086, vs. “pandemic outbreak”). The incidence of PNS‐associated antibodies was unaffected by the COVID‐19 pandemic. Conclusions The increased incidence of AE‐associated antibodies during the COVID‐19 “pandemic outbreak” suggests a potential biological link. The subsequent decline in incidence in the “mid to late pandemic” period may be attributable to widespread vaccination and the emergence of new viral variants with less potential to induce autoimmunity. The incidence of PNS‐associated antibodies was stable throughout, reinforcing its primary association with malignancy.